The Role of Leadership in Building a Positive Work Ethic at Intan Al-Sali Elementary School - Muftiyyatul Ummah; Wahyu Hidayat (al-Afkar, Journal For Islamic Studies, 2026)
Leadership plays a strategic role in shaping a positive work culture within educational settings. A positive work ethic is a crucial foundation for improving the performance quality of teachers and staff. However, challenges in implementing good work values, such as low motivation and lack of synergy among individuals, require an effective leadership approach. This study aims to analyze the role of school principals' leadership in fostering a positive work ethic. The research focuses on identifying leadership strategies applied, their impact on the motivation of teachers and staff, and the challenges faced in the process. This study employs a qualitative approach with data collected through in-depth interviews, observations, and documentation. The data were analyzed using qualitative descriptive techniques to uncover relevant leadership patterns. The findings reveal that the transformational leadership of school principals significantly contributes to building a positive work ethic. Strategies such as effective communication, recognition, and regular training successfully enhance the motivation and productivity of teachers and staff. Challenges encountered include resistance to change and resource limitations. This study recommends strengthening leadership training and improving supporting facilities to further enhance a positive work ethic within schools.